2019
DOI: 10.1186/s12986-019-0359-2
|View full text |Cite
|
Sign up to set email alerts
|

Caprylic acid suppresses inflammation via TLR4/NF-κB signaling and improves atherosclerosis in ApoE-deficient mice

Abstract: Background As reported previously by our group, medium-chain triglycerides can ameliorate atherosclerosis. Given that TLR4 is closely related to atherosclerosis, we hypothesized herein that caprylic acid (C8:0) would suppress inflammation via TLR4/NF-κB signaling and further promote the amelioration of atherosclerosis in apoE- deficient (apoE −/− ) mice. Methods Fifty 6-week male apoE −/− mice were randomly allocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 58 publications
4
35
0
Order By: Relevance
“…Chronic inflammation plays an important role in the development of PCOS ( 31 , 32 ). The TLR4/NF-κB pathway has distinct functions during the stress reaction and inflammation ( 33 ). Several studies have demonstrated that HMGB1 could trigger the TLR4 signaling pathway and NF-κB activation, thereby inducing the expression of inflammatory factors ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation plays an important role in the development of PCOS ( 31 , 32 ). The TLR4/NF-κB pathway has distinct functions during the stress reaction and inflammation ( 33 ). Several studies have demonstrated that HMGB1 could trigger the TLR4 signaling pathway and NF-κB activation, thereby inducing the expression of inflammatory factors ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that THD could exert the antiinflammatory effect through ERK5/STAT3 pathway. AKT plays a role in inflammation-associated diseases (Yan et al, 2018) and NF-kB p65 is a treatment target to control inflammation (Zhou et al, 2014;Zhang et al, 2019). Activated NF-kB can be translocated into nucleus, then the phosphorylated NF-kB becomes the transcription factors of inflammatory genes (Viatour et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the anti-inflammatory effects of lauric acid and caprylic acid [14,15]. Choline upregulated lipid synthesis in vitro in an experimental model of transepidermal diffusion, providing a functional assessment of skin barrier properties [16]. Roth-Walter et al reported that iron-deficient conditions can induce a Th2 environment, which contributes to the pathogenesis of allergies [17].…”
Section: Introductionmentioning
confidence: 99%